Coefficient of restitution of colliding viscoelastic spheres - Ramirez, Rosa; Pöschel, Thorsten; Brilliantov, Nikolai; Schwager, Thomas (Physical Review E, 1999)
We perform a dimension analysis for colliding viscoelastic spheres to show that the coefficient of normal restitution ε depends on the impact velocity g as ε=1-γg+γg+ ⋯, in accordance with recent findings. We develop a simple theory to find explicit expressions for coefficients γ and γ. Using these and few next expansion coefficients for ε(g) we construct a Padé approximation for this function which may be used for a wide range of impact velocities where the concept of the viscoelastic collision is valid. The obtained expression reproduces quite accurately the existing experimental dependence ε(g) for ice particles.